Microwave Power Beaming using Ka-band Radar Tethered Aerostat Program - Haugstad, Travis D; Rudy, Landon; Watson, Nicholas; LePlante, Brian (Proceedings of the Wisconsin Space Conference, 2017)
With electronic devices becoming smaller and more portable, they are being utilized more in science and everyday life.Â  There must be a way to power these devices without long cables, large batteries, or other power supplies. Mobile phones and CubeSats are examples of technologies that could take advantage of wireless low-energy transfer for powering or charging devices. Our platform, containing our receiving circuitry was suspended from a tethered aerostat. The platform was designed to receive the wireless signal emitted from a microwave transmitter, analyze the strength of the signal via a programmable microcontroller, and transmit the data back to our logging station on ground level. In order to receive the transmitted power in a usable state, a rectifier and multiple antennas had to be designed and built to test for reception and efficiency. The antennas designed included the Yagi-Uda and fractal-patch antennas